An unusual case of subdural haematoma presenting to the accident and emergency department. Issue 4 (1st July 2001) - Chillala, S; Read, C; Evans, P A
Abstract : A case of subdural haematoma associated with an intracranial arachnoid cyst is reported. The pathogenesis, clinical presentation and treatment options of intracranial arachnoid cysts is discussed.